EF (Efficient Fibre) Sago Compound for 3D Modeling Products - Saiful Bahari, Mohd Yusoff; Hamdan, Sinin; Yeeni Ayu Rosita, Marjani; Zalina, Ibrahim; Mohamad Hariri, Abdullah (UNIMAS Publisher, Universiti Malaysia Sarawak, 2019)
EF (Efficient Fibre) Sago Compound is created using sago waste to produce an environmental friendly compound that can be used for 3D modelling products. EF Sago Compound can be a substitute material to the hazardous floral foam and woods in creating 3D models products. EF Sago Compound is found to be safer material that is light, soft, durable, cheap, can be easily cut and shaped. In research context, EF Sago Compound is the first compound created using sago waste meant for modelling work. This material is found to cheaper version of modelling/product material. As well as environmental friendly material for modelling/product material. For commercial potential, this material can be used for any modeling work, able to create safer compound compared to existing materials. Variety of products and finishes will be able to be created by using the EF Sago Compound product.